2018
DOI: 10.1093/biolre/ioy228
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal response of juvenile protogynous grouper (Epinephelus fuscoguttatus) to long-term recombinant follicle-stimulating hormone administration†

Abstract: Gonadal response of juvenile protogynous grouper (Epinephelus fuscoguttatus) to long term recombinant follicle-stimulating hormone administration Running title: Gonadal response of juvenile grouper to rggFSH Summary sentence: Administration of recombinant grouper FSH to juvenileprotogynous grouper promoted oocyte development to the cortical alveolar stage, and initiated female to male sex change while suppressing steroidogenic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 64 publications
(99 reference statements)
4
13
0
Order By: Relevance
“…It has also been reported in E. coioides that endogenous 11KT triggers their natural sex change from female to male 26 . Additionally, a novel experimental study on E. fuscoguttatus suggested that pituitary FSH is involved in the initiation of sex change as an upstream factor, which is consistent with our previous findings regarding the honeycomb grouper 17 , 27 . Considering these findings, we suggest that sex change in groupers is regulated by a common endocrine mechanism: 11KT, which is secreted from TIS cells in response to pituitary FSH, triggers the onset of sex change, as previously reported in the honeycomb grouper (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…It has also been reported in E. coioides that endogenous 11KT triggers their natural sex change from female to male 26 . Additionally, a novel experimental study on E. fuscoguttatus suggested that pituitary FSH is involved in the initiation of sex change as an upstream factor, which is consistent with our previous findings regarding the honeycomb grouper 17 , 27 . Considering these findings, we suggest that sex change in groupers is regulated by a common endocrine mechanism: 11KT, which is secreted from TIS cells in response to pituitary FSH, triggers the onset of sex change, as previously reported in the honeycomb grouper (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In orange-spotted grouper Epinephelus coioides, recombinant FSH injection resulted in the occurrence of primary oocytes in sexually immature individuals (Chen et al 2012). Similarly, our previous experiments showed that recombinant FSH injection advanced oocyte development into cortical alveolar stage in juvenile tiger grouper although prolonged treatment resulted in the initiation of female to male sex change (Palma et al 2019a). Female vitellogenic honeycomb grouper Epinephelus merra also sex reversed after receiving injection of bovine FSH (Kobayashi et al 2010).…”
Section: Introductionmentioning
confidence: 59%
“…For instance, after 60 days of treatment with injections at 10-day intervals of rFsh produced in P. pastoris (10 -20 µg kg-1) immature yellowtail kingfish oocytes developed to cortical alveoli stage (Sanchís-Benlloch et al, 2017). Weekly injections for 8 weeks at 100 µg kg-1 to juvenile grouper (Epinephelus fuscoguttatus) also induced development to the cortical alveoli stage (Palma et al, 2018). Recombinant Fsh produced in Drosophila S2 cell line (100 µg kg-1) induced early vitellogenesis in the Japanese eel after 56 days of treatment with a weekly administration (Kazeto et al, 2008) and rFsh (500 µg/kg) produced in HEK293 cells induced initial oil droplet stage in previtellogenic yellow shortfinned eels (Anguilla australis) after three weeks (Tuan Nguyen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative strategy to control gametogenesis in mullet as in other teleost, which would not require the availability of endogenous Gths from the pituitary, is the long-term use of recombinant Fsh and Lh (rFsh and rLh, respectively). This approach is nowadays possible through the production of large amounts of species-specific rGths in heterologous expression systems, such as the Drosophila S2 cell line (Kazeto et al, 2008;Zmora et al, 2007), the yeast Pichia pastoris (Aizen et al, 2007;Chen et al, 2012;Kamei et al, 2003;Kasuto and Levavi-Sivan, 2005;Palma et al, 2018;Sanchís-Benlloch et al, 2017), baculovirus silkworm larvae (Cui et al, 2007;Glubokov et al, 1994;Ko et al, 2007;Kobayashi et al, 2010Kobayashi et al, , 2003Meri et al, 2000), HEK293 cells (Kazeto et al, 2019) and…”
Section: Introductionmentioning
confidence: 99%